The Use of Additive Manufacturing for Wind Tunnel Simulations - Pálfi, Tamás; Ficzere, Péter (International Journal of Engineering and Management Sciences, 2022)
The current economical situation requires aircraft operators to start organizing their activity in the direction of carbon neutrality using innovative solutions. The goal of present study is to desing a brand new wingtip device using 3D printing which helps reducing aerodynamical drag, leading to fuel efficiency and less carbon emission with its innovative shape.